Generation of isolated attosecond pulses in CdS semiconductor using polarization gating technique and tailored two-color pulse system - Amin Sadeghifaraz; Elnaz Irani (Scientific Reports)
Abstract This research uses a two-color pulse system and polarization gating technique to generate single attosecond pulses from femtosecond laser interaction with cadmium sulfide semiconductor. The rotating elliptical polarization two-color pulse system is designed to produce attosecond pulses up to 420 as. Also, the intensity of the single attosecond pulse can be improved by using a two-color-polarizing gate technique. In this presented modifications, the isolated attosecond pulse with greater intensity and a shorter time width of about 400 as is generated. Generation of such an intense isolated attosecond pulse is a great achievement that helps for measuring the ultrafast phenomena.